Synthesis, cytotoxicities, and carbonic anhydrase inhibition potential of 6-(3-aryl-2-propenoyl)-2(3H)-benzoxazolones - Sinan Bilginer; Halise Inci Gul; Feyza Sena Erdal; Hiroshi Sakagami; Serkan Levent; Ilhami Gulcin; Claudiu T. Supuran (Taylor & Francis Group, 2019)
In this study, new chalcone compounds having the chemical structure of 6-(3-aryl-2-propenoyl)-2(3H)-benzoxazolones (1-8) were synthesised and were characterised by 1H-NMR, 13 C-NMR, and HRMS spectra. Cytotoxic and carbonic anhydrase (CA) inhibitory effects of the compounds were investigated. Cytotoxicity results pointed out that compound 4, 6-[3-(4-trifluoromethylphenyl)-2-propenoyl]-3H-benzoxazol-2-one, showed the highest cytotoxicity (CC50) and potency-selectivity expression (PSE) value, and thus can be considered as a lead compound of this study. According to the CA inhibitory results, IC50 values of the compounds 1-8 towards hCA I were in the range of 29.74-69.57 µM, while they were in the range of 18.14 - 48.46 µM towards hCA II isoenzyme. Ki values of the compounds 1-8 towards hCA I were in the range of 28.37 ± 6.63-70.58 ± 6.67 µM towards hCA I isoenzyme and they were in the range of 10.85 ± 2.14 - 37.96 ± 2.36 µM towards hCA II isoenzyme.